2023
DOI: 10.3390/v15102084
|View full text |Cite
|
Sign up to set email alerts
|

Deacetylation of ACO2 Is Essential for Inhibiting Bombyx mori Nucleopolyhedrovirus Propagation

Miao Hu,
Yi You,
Yao Li
et al.

Abstract: Bombyx mori nucleopolyhedrovirus (BmNPV) is a specific pathogen of Bombyx mori that can significantly impede agricultural development. Accumulating evidence indicates that the viral proliferation in the host requires an ample supply of energy. However, the correlative reports of baculovirus are deficient, especially on the acetylation modification of tricarboxylic acid cycle (TCA cycle) metabolic enzymes. Our recent quantitative analysis of protein acetylome revealed that mitochondrial aconitase (ACO2) could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Furthermore, studies have identified numerous acetylation sites within TCA cycle proteins. These modifications can influence protein activity, with some experiencing increased activity and others experiencing decreased activity [19,40,41]. For example, acetylation of A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studies have identified numerous acetylation sites within TCA cycle proteins. These modifications can influence protein activity, with some experiencing increased activity and others experiencing decreased activity [19,40,41]. For example, acetylation of A.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have identified numerous acetylation sites within TCA cycle proteins. These modifications can influence protein activity, with some experiencing increased activity and others experiencing decreased activity [19, 40, 41]. For example, acetylation of A. thaliana malate dehydrogenase at K169, K170, and K334 decreases its oxoacetate reduction activity [42], while acetylation of E. coli and H. sapiens at K99/K140 and K307, respectively, increases its enzymatic activity [43].…”
Section: Discussionmentioning
confidence: 99%